Health-related social media use and COVID-19 anxiety in adolescence: health anxiety as covariate and moderator - Lokajova, Adela; Smahel, David; Kvardova, Nikol (Frontiers in Psychology, 2023)
Background Adolescents can benefit from engagement with health-related content on social media (e.g., viewing, commenting, or sharing content related to diseases, prevention, or healthy lifestyle). Nevertheless, such content may be distressing or exaggerated and present a challenge to mental well-being, especially during the COVID-19 pandemic. Rumination about such content may lead to COVID-19 anxiety. Yet, the individual factors that would explain the association between health-related social media use (SMU) and COVID-19 anxiety are understudied. Objective In the current study, we aimed to fill the gap by investigating the association between health-related social media use (SMU) and COVID-19 anxiety in light of several individual factors: health anxiety, eHealth literacy, and mild and severe experience with COVID-19 infection. We (1) studied the relationship between individual factors and health-related SMU, (2) tested health anxiety as a moderator in the association between health-related SMU and COVID-19 anxiety, and (3) explored a direct effect of experience with COVID-19 on COVID-19 anxiety. Methods Using structural equation modeling, we analyzed cross-sectional data from a representative sample of 2,500 Czech adolescents aged 11–16, 50% girls. Sociodemographic measures, health-related SMU, COVIDCOVID-19 anxiety, health anxiety, eHealth literacy, and mild and severe experience with COVID-19 infection were assessed with an anonymous online survey. The data were collected in June 2021. Results We conducted a path analysis to test the main relationships and an additional simple-slopes analysis to explore the moderating effect of health anxiety. Higher health anxiety and eHealth literacy were associated with increased health-related SMU. The effect of experience with COVID-19 infection on both COVID-19 anxiety and health-related SMU was negligible. Health-related SMU and COVID-19 anxiety were positively associated, however, only for adolescents high in health anxiety. For other adolescents, the two variables were unrelated. Conclusion Our findings show that adolescents with higher health anxiety and eHealth literacy engage in health-related SMU more intensively. Furthermore, for adolescents high in health anxiety, the frequency of health-related SMU is associated with the risk of COVID-19 anxiety. This is likely due to differences in media use. Adolescents with high health anxiety may use social media for content that is more likely to lead to COVID-19 anxiety compared to other adolescents. We recommend focusing on the identification of such content, which may lead to more precise recommendations regarding health-related SMU compared to cut-back on the frequency of overall SMU.